FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN PEMERINTAH DAERAH DI DAERAH ISTIMEWA YOGYAKARTA MENERBITKAN OBLIGASI DAERAH - , GUNAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Local government financing receipt in 2007-2011 largely derived from the balance over the previous year's budget calculations, whereas those loans and municipal bonds is only about 1 to 6 percent. This suggests that local governments do not tend to use financing from municipal debt and municipal bonds. To support the implementation of the issuance of municipal bonds, the government has issued Regulation of the Minister of Finance No. 147/PMK.07/2006 dated December 29, 2006 on Procedures for Issuance, Responsibility, and Publication of Municipal Bond Information. The various regulations of the underlying municipal bond issuance has indeed provided an opportunity to the local government, including local government in Yogyakarta to issue municipal bonds. This study aims to identify and analyze the factors that explain the readiness of local governments in Yogyakarta to issue municipal bonds. Data was collected through questionnaire distribution using purposive sampling techniques and unstructured interviews were conducted. To identify the factors used exploratory factor analysis and to analyze the results of the factors identify used qualitative descriptive analysis. The results of the factor analysis shows that there are five factors that explain the readiness of local governments in Yogyakarta to issue municipal bonds, namely: project readiness factor, human resource capacity factor, management principles factor, mechanism, requirement and sanction factor, and the capability of the local financial factor. The results of the qualitative descriptive analysis indicate that the projects that are undertaken are generally social and service as well as projects that have been programmed by the Government that is not profit-oriented. Projects financing that inadequately funded from local government budget are generally requested funds to the Government. Local government are still limited to carrying out routine tasks and do not dare to do new things that are innovative, complex and risky. Leader and middle-level do not understand about municipal bonds. No dissemination to local governments that are active, meaningful, and face to face. Local government in Yogyakarta have not been supported with adequate human resources. Local government in Yogyakarta is still limited to the use of the existing budget. The budget structure dominated for personnel expenses resulting not have the funds to prepare for the issuance of bonds.